2020
DOI: 10.1101/2020.05.04.076042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining sex-differentiated genetic effects across neuropsychiatric and behavioral traits

Abstract: Background:The origin of sex differences in prevalence and presentation of neuropsychiatric and behavioral traits is largely unknown. Given established genetic contributions and correlations across these traits, we tested for a sex-differentiated genetic architecture within and between traits. Methods:Using genome-wide association study (GWAS) summary statistics for 20 neuropsychiatric and behavioral traits, we tested for differences in SNP-based heritability (h 2 ) and genetic correlation (rg<1) between sexes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…These were 10 predominantly adult-afflicting psychiatric comorbidities for which ICD code definitions had previously been validated. 29 The prevalence of most of these psychiatric comorbidities in the VUMC-EHR was similar to previously reported literature. However, prevalence of these psychiatric comorbidities was much higher in patients with functional seizures, ranging from 2.6% (phobia) to 30.2% (major depressive disorder).…”
Section: Resultssupporting
confidence: 89%
“…These were 10 predominantly adult-afflicting psychiatric comorbidities for which ICD code definitions had previously been validated. 29 The prevalence of most of these psychiatric comorbidities in the VUMC-EHR was similar to previously reported literature. However, prevalence of these psychiatric comorbidities was much higher in patients with functional seizures, ranging from 2.6% (phobia) to 30.2% (major depressive disorder).…”
Section: Resultssupporting
confidence: 89%
“…Rather, the results indicate that any sex differences in disease signature are likely small and will require additional analyses in larger sample sizes. This notion is further supported by recent work on large-scale genome-wide association studies (GWAS) of schizophrenia (44)(45)(46). These studies did not identify genome-wide significant effect size differences between males and females and the genetic correlation between males and females is statistically not different from 1.0.…”
Section: Discussionmentioning
confidence: 66%
“…These studies did not identify genome-wide significant effect size differences between males and females and the genetic correlation between males and females is statistically not different from 1.0. More broadly, in analyses of large-scale GWAS and biobank data, findings of sex-specific effects or differences in heritability between males and females have been limited (44,46,47). These negative results from otherwise well-powered datasets underscore the challenge of studying the molecular mechanisms underlying clinical differences in schizophrenia between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…While this analysis was not significant in the NCMH data, the point estimate was actually higher in the early onset group analysis in NCMH [OR=1.17(0.93–1.47)] compared to PGC [OR=1.08(1.02–1.15)], indicating that the lower power of the smaller NCMH sample to detect such a small effect may have impacted on the lack of consistency in terms of statistical significance. This study also adds to other cross-disorder analyses of common genetic variants, which show moderate genetic correlations across ADHD, anxiety and depression, with no significant sex differences observed across these genetic correlations (11,12).…”
Section: Discussionmentioning
confidence: 70%
“…Genome-wide association studies (GWAS) have identified robustly associated risk alleles for both disorders, accounting for 26% of variance in anxiety and 8.7% of variance in major depressive disorder (MDD) (9,10). The genetic correlation between males and females is very high for each of these disorders and there are no SNPs identified to date showing a genome-wide significant sex difference in allele frequency (11). GWAS have also demonstrated that a significant proportion of the genetic liabilities of anxiety and MDD are shared with other psychiatric disorders in males and females (912).…”
Section: Introductionmentioning
confidence: 99%